Metabolic synthetic lethality by targeting NOP56 and mTOR in KRAS-mutant lung cancer - Zhang Yang; Shun-Qing Liang; Liang Zhao; Haitang Yang; Thomas M. Marti; Balazs Hegedüs; Yanyun Gao; Bin Zheng; Chun Chen; Wenxiang Wang; Patrick Dorn; Gregor J. Kocher; et al. (Journal of Experimental & Clinical Cancer Research, 2022)
Abstract Background Oncogenic KRAS mutations are prevalent in human cancers, but effective treatment of KRAS-mutant malignancies remains a major challenge in the clinic. Increasing evidence suggests that aberrant metabolism plays a central role in KRAS-driven oncogenic transformation. The aim of this study is to identify selective metabolic dependency induced by mutant KRAS and to exploit it for the treatment of the disease. Method We performed an integrated analysis of RNAi- and CRISPR-based functional genomic datasets (n = 5) to identify novel genes selectively required for KRAS-mutant cancer. We further screened a customized library of chemical inhibitors for candidates that are synthetic lethal with NOP56 depletion. Functional studies were carried out by genetic knockdown using siRNAs and shRNAs, knockout using CRISPR/Cas9, and/or pharmacological inhibition, followed by cell viability and apoptotic assays. Protein expression was determined by Western blot. Metabolic ROS was measured by flow cytometry-based quantification. Results We demonstrated that nucleolar protein 5A (NOP56), a core component of small nucleolar ribonucleoprotein complexes (snoRNPs) with an essential role in ribosome biogenesis, confers a metabolic dependency by regulating ROS homeostasis in KRAS-mutant lung cancer cells and that NOP56 depletion causes synthetic lethal susceptibility to inhibition of mTOR. Mechanistically, cancer cells with reduced NOP56 are subjected to higher levels of ROS and rely on mTOR signaling to balance oxidative stress and survive. We also discovered that IRE1α-mediated unfolded protein response (UPR) regulates this process by activating mTOR through p38 MAPK. Consequently, co-targeting of NOP56 and mTOR profoundly enhances KRAS-mutant tumor cell death in vitro and in vivo. Conclusions Our findings reveal a previously unrecognized mechanism in which NOP56 and mTOR cooperate to play a homeostatic role in the response to oxidative stress and suggest a new rationale for the treatment of KRAS-mutant cancers.